Factors Behind Low Political Participation of Females in Pakistan - Begum, Azeema (International Journal on Women Empowerment, 2023)
Background: Since women constitute approximately half of the population in Pakistan, it is essential for the country's economic growth and social development for women to be actively involved in the political system. Despite the large percentage of the population, women in Pakistan have historically encountered discrimination in both the economic and political spheres. This research examines the significant factors of low female political participation in Pakistan. Methodology: This study has used a qualitative research method using a desk-based study, which included articles, research papers, and other official websites as secondary sources. Results: It has been found that there are several factors, such as political, religious, economic, gender discrimination, ideological, and cultural, that restrict female participation in the political process. Conclusion: The role of women should be more concentrated via normative practices at the local and societal level, as well as the promotion of education and awareness, to increase female participation in politics.